Effectiveness of mRNA-1273 against delta, mu, and other emerging variants of SARS-CoV-2: test negative case-control study. (15th December 2021) - Bruxvoort, Katia J; Sy, Lina S; Qian, Lei; Ackerson, Bradley K; Luo, Yi; Lee, Gina S; Tian, Yun; Florea, Ana; Aragones, Michael; Tubert, Julia E; Takhar, Harpreet S; Ku, Jennifer H; et al.
Abstract: Objectives: To evaluate the effectiveness of the mRNA-1273 vaccine against SARS-CoV-2 variants and assess its effectiveness against the delta variant by time since vaccination. Design: Test negative case-control study. Setting: Kaiser Permanente Southern California (KPSC), an integrated healthcare system. Participants: Adult KPSC members with a SARS-CoV-2 positive test sent for whole genome sequencing or a negative test from 1 March 2021 to 27 July 2021. Interventions: Two dose or one dose vaccination with mRNA-1273 (Moderna covid-19 vaccine) ≥14 days before specimen collection versus no covid-19 vaccination. Main outcome measures: Outcomes included infection with SARS-CoV-2 and hospital admission with covid-19. In pre-specified analyses for each variant type, test positive cases were matched 1:5 to test negative controls on age, sex, race/ethnicity, and specimen collection date. Conditional logistic regression was used to compare odds of vaccination among cases versus controls, with adjustment for confounders. Vaccine effectiveness was calculated as (1–odds ratio)×100%. Results: The study included 8153 cases and their matched controls. Two dose vaccine effectiveness was 86.7% (95% confidence interval 84.3% to 88.7%) against infection with the delta variant, 98.4% (96.9% to 99.1%) against alpha, 90.4% (73.9% to 96.5%) against mu, 96-98% against other identified variants, and 79.9% (76.9% to 82.5%) against unidentified variants (that is, specimens that failed sequencing). Vaccine effectiveness against hospital admission with the delta variant was 97.5% (92.7% to 99.2%). Vaccine effectiveness against infection with the delta variant declined from 94.1% (90.5% to 96.3%) 14-60 days after vaccination to 80.0% (70.2% to 86.6%) 151-180 days after vaccination. Waning was less pronounced for non-delta variants. Vaccine effectiveness against delta infection was lower among people aged ≥65 years (75.2%, 59.6% to 84.8%) than those aged 18-64 years (87.9%, 85.5% to 89.9%). One dose vaccine effectiveness was 77.0% (60.7% to 86.5%) against infection with delta. Conclusions: Two doses of mRNA-1273 were highly effective against all SARS-CoV-2 variants, especially against hospital admission with covid-19. However, vaccine effectiveness against infection with the delta variant moderately declined with increasing time since vaccination.